The Research progress on the effect of gut microbiota changes on postoperative renal transplantation patients - ZHENG Yaxin; ZHOU Fengying; ZOU Yaoshuang; CHEN Huaizhou; GUO Junjun; LAI Liusheng; TANG Donge; DAI Yong; YAN Qiang (Guangxi Yike Daxue xuebao)
A series of complications such as diarrhea, infection and rejection are easy to occur after renal transplantation, which seriously affects the survival rate of the grafts and the survival rate of patients after renal transplantation. With the development of metagenomics, numerous studies have proved that the composition, structure and function of gut microbiota in patients after transplantation have changed correspondingly and related to posttransplant complications. This review summarizes the studies on the association between the changes of gut microbiota after renal transplantation and the post-transplant complications, as well as the treatment methods for post-transplant complications in recent years, and also puts forward prospects.